User Privacy in the Age of Mobile Browsing: A Literature Review of Data Tracking and Protection Policies - Karin, Juliana (Universitas Komputer Indonesia, 2024)
The rapid evolution of mobile computing has transformed the smartphone into a primary gateway for internet access, simultaneously turning it into a rich source of granular personal data. This literature review examines the current landscape of user privacy within mobile browsing environments, focusing on the sophisticated mechanisms of data tracking and the efficacy of modern protection policies. As mobile browsers integrate more deeply with OS-level sensors and location services, the surface area for unauthorized data harvesting has expanded beyond traditional web cookies to include browser fingerprinting and cross-app tracking. This paper synthesizes recent research to evaluate the tension between personalized web experiences and the fundamental right to privacy. We analyze the impact of major regulatory frameworks, such as GDPR and CCPA, against the technical reality of